Making the People's landscape: Landscape ideals, collective labour, and the People's parks (Folkets Parker) movement in Sweden, 1891-present. (April 2021) - Mitchell, Don; Jönsson, Erik; Pries, Johan
Abstract: Beginning in the 1890s, workers' associations and social-democratic activists in Sweden developed a series of People's Parks ( Folkets p arker ) that extended across the length and breadth of the country. By the the mid-twentieth century, nearly every city, town, and village boasted its own People's Park. Built for relaxation and recreation, as well as for political agitation, Folkets p arker also represented a significant expropriation and transformation of bourgeois landscape ideals and in the process became places where a new, working class-based folk, or people, could come to be. This paper traces the production of Folkets p arker as landscape, focusing on the ways in which working people reworked landscape ideals in order to contest bourgeois constructions of Swedish national identity, while asserting their own power to shape that identity. We argue that working people traded in, and transformed, two landscape ideas – one rooted in bourgeois notions of the rural idyll and the other rooted in an older more specifically Scandinavian tradition of landscape as a shaped space belonging to those who shaped it. But we also show how, as the social-democratic state consolidated its hegemony in the middle-twentieth century, the underlying material basis for shaping the parks as landscape was transformed. Folkets p arker became places primarily for recreation and entertainment and their status as shaped spaces that shaped identity faded. Highlights: Revises history of Sweden's Folkets Parker movement. Explores how landscape ideals are refashioned by the working class. Exposes part of the material basis for Sweden's folkhem. Revises understandings of how – and why – working people produce landscapes.